The Lion, the witch and the wardrobe a story for children - Lewis, Clive Staples 1898-1963.; Baynes, Pauline (New York Macmillan, 1950)
Four school children find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.
Keywords: Fantasy